2020
DOI: 10.1159/000505956
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular Transcriptome Profiles in Focal Glomerulosclerosis: New Genes and Pathways for Steroid Resistance

Abstract: Background: Patients with focal segmental glomerulosclerosis (FSGS) characterized by steroid-resistant nephrotic syndrome (SRNS) are prone to progress to ESRD. Mechanism for the FSGS patients' response to steroid treatment is still unknown and currently, it is impossible to predict the steroid resistance before treatment of patients with FSGS. Methods: To identify biomarkers and potential therapeutic targets of FSGS patients with SRNS, patients diagnosed as kidney biopsy-proven FSGS and nephrotic syndrome (NS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The concentration of H 2 O 2 was assessed using a Hydrogen Peroxide Assay kit (Beyotime, Catalogue No. S0038) (n = 6) according to the previously described protocol [31][32][33]. For the in vivo experiment, heart tissues in the border zone were collected, homogenised, and lysed in lysis buffer.…”
Section: Oxidative Stress Assessmentmentioning
confidence: 99%
“…The concentration of H 2 O 2 was assessed using a Hydrogen Peroxide Assay kit (Beyotime, Catalogue No. S0038) (n = 6) according to the previously described protocol [31][32][33]. For the in vivo experiment, heart tissues in the border zone were collected, homogenised, and lysed in lysis buffer.…”
Section: Oxidative Stress Assessmentmentioning
confidence: 99%
“…In addition to mitochondrial respiratory chain dysfunction, high activity of NOX also accounts for increased ROS levels. Recently, a study in FSGS patients showed that steroid-resistant FSGS patients had higher NOX4 levels as well as higher ROS levels in isolated glomeruli compared to steroid-sensitive nephrotic syndrome patients [25] . By antagonizing the upregulation of NOX expression and downregulation of nuclear factor erythroid 2-related factor 2 (Nrf2) expression, angiotensin II receptor blockers exhibited a therapeutic effect, improving OS and inflammation in spontaneous FSGS Imai rats [26] (shown in Fig.…”
Section: Mitochondrial Abnormalities In Fsgsmentioning
confidence: 99%
“…Patients were divided into two groups, steroid-sensitive and non-sensitive, depending on their response. In the results, MAPK/MMP-2 was observed to be upregulated in glomeruli isolated from steroid-non-sensitive patients [ 99 ].…”
Section: Biomarkers Potentially Contributed To Podocyte Injury or Cel...mentioning
confidence: 99%